2007
DOI: 10.1037/0003-066x.62.2.118
|View full text |Cite
|
Sign up to set email alerts
|

The dirty dozen: Twelve failures of the Hurricane Katrina response and how psychology can help.

Abstract: This comprehensive analysis addresses the United States' alarming lack of preparedness to respond effectively to a massive disaster as evidenced by Hurricane Katrina. First, a timeline of problematic response events during and after Hurricane Katrina orients readers to some of the specific problems encountered at different levels of government. Second, a list of the "Dirty Dozen"--12 major failures that have occurred in prior disasters, which also contributed to inadequate response during and after Hurricane K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 61 publications
(58 reference statements)
2
77
0
Order By: Relevance
“…Going beyond an extreme event, we define an extreme context as an environment where one or more extreme events are occurring or are likely to occur that may exceed the organization's capacity to prevent and result in an extensive and intolerable magnitude of physical, psychological, or material consequences to-or in close physical or psycho-social proximity to-organization members. 4 Examples include the Mann Gulch (Weick, 1993) and South Canyon fires (Useem, Cook, & Sutton, 2005), Indian Ocean Tsunami (Athukorala & Resosudarmo, 2005;Rodriquez, Wachtendorf, Kendra, & Trainor, 2006), Bhopal Chemical release (Bowman & Kunreuther, 1988;Shrivastava, 1987;Union Carbide Report, 1985), Three Mile Island meltdown (Hopkins, 2001;Perrow, 1997), Columbia Space Shuttle explosion (Heimann, 1993;Starbuck & Miliken, 1988;Vaughan, 1996), Westray mine disaster (Hynes & Prasad, 1997), Mount Everest climbing incidents (Kayes, 2004;Tempest, Starkey, & Ennew, 2007), hurricane Katrina (Comfort, 2007;Gheytanchi et al, 2007;Kapucu & Van Wart, 2006;Rego & Garau, 2007), Tenerife airplane collision (Weick, 1990), Chernobyl (Hohenemser, Deicher, Ernst, Hofsäss, Lindner, & Recknagel (1986)), numerous military leadership and combat studies (e.g., Cosby et al, 2006;Morath, Ccurnow, Cronin, Leonard, & McGonigle, 2006;Leonard, Polich, Peterson, Sorter, & Moore, 2006;Department of the Army, 1950Scales, 2006;Snook, 2000;Ulmer, Shaler, Bullis, DiClemente, & Jacobs, 2004;Wong, Bliese, & McGurk, 2003) and organizational doctrine such as the U. S. Army (Department of the Army, 2006) and National Wildfire Service (2007) leadership manuals.…”
Section: Defining Extreme Events and Extreme Contextsmentioning
confidence: 99%
“…Going beyond an extreme event, we define an extreme context as an environment where one or more extreme events are occurring or are likely to occur that may exceed the organization's capacity to prevent and result in an extensive and intolerable magnitude of physical, psychological, or material consequences to-or in close physical or psycho-social proximity to-organization members. 4 Examples include the Mann Gulch (Weick, 1993) and South Canyon fires (Useem, Cook, & Sutton, 2005), Indian Ocean Tsunami (Athukorala & Resosudarmo, 2005;Rodriquez, Wachtendorf, Kendra, & Trainor, 2006), Bhopal Chemical release (Bowman & Kunreuther, 1988;Shrivastava, 1987;Union Carbide Report, 1985), Three Mile Island meltdown (Hopkins, 2001;Perrow, 1997), Columbia Space Shuttle explosion (Heimann, 1993;Starbuck & Miliken, 1988;Vaughan, 1996), Westray mine disaster (Hynes & Prasad, 1997), Mount Everest climbing incidents (Kayes, 2004;Tempest, Starkey, & Ennew, 2007), hurricane Katrina (Comfort, 2007;Gheytanchi et al, 2007;Kapucu & Van Wart, 2006;Rego & Garau, 2007), Tenerife airplane collision (Weick, 1990), Chernobyl (Hohenemser, Deicher, Ernst, Hofsäss, Lindner, & Recknagel (1986)), numerous military leadership and combat studies (e.g., Cosby et al, 2006;Morath, Ccurnow, Cronin, Leonard, & McGonigle, 2006;Leonard, Polich, Peterson, Sorter, & Moore, 2006;Department of the Army, 1950Scales, 2006;Snook, 2000;Ulmer, Shaler, Bullis, DiClemente, & Jacobs, 2004;Wong, Bliese, & McGurk, 2003) and organizational doctrine such as the U. S. Army (Department of the Army, 2006) and National Wildfire Service (2007) leadership manuals.…”
Section: Defining Extreme Events and Extreme Contextsmentioning
confidence: 99%
“…Ineffectual communications or breakdowns in the channels along which information is conveyed have been cited as significant factors in the inadequate or failed response to previous natural disasters, including, for example, the Easter and summer floods of 1998 and 2007 in the UK (Horner and Walsh, 2000;Pitt, 2007) and the floods that resulted from Hurricane Katrina in 2005 (Gheytanchi et al, 2007). The reasons for failed communications are diverse.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that when determining who are most vulnerable to psychosocial impacts of climate change, research on disaster intervention has identified groups to be at greater risk including children, the elderly, rural and urban poor, racial and ethnic minorities, those with a previous history of emotional disability, and, in general, those with a marginalized pre-disaster existence (Gheytanchi et al, 2007;Bourque et al, 2006) …”
Section: Differential Physical and Psychosocial Effects On Vulnerablementioning
confidence: 99%